A study on predictive factors for anastomotic leakage in enteropancreatic anastomosis in a tertiary centre in Andhra Pradesh - Desu, Bharath Kumar; Kunnuru, Supreeth Kumar Reddy; Gurjar, Mayank Kumar; Palanati, Varun; Salavakam, Muni Krishna; R., Rakesh; Varty, Gurudutt P.; Challapalli, Praneeth Reddy; S., Thirunavukkarasu (International Surgery Journal, 2019)
Background: This study aimed to identify various factors influencing occurrence of post-operative pancreatic fistula. Methods: Only those patients who underwent standard pancreatojejunostomy anastomosis in duct to mucosa technique using vicryl 4-0 sutures (double layer- interrupted fashion) were included in the study. Patients who had duct size ≤3 mm underwent papillary like main pancreatic duct invaginated technique of pancreaticojejunostomy (fish mouth type). Results: In 40 patients, 10 patients (25%) developed postoperative pancreatic fistula. 5 (12.5%) patients had grade A pancreatic fistula and 5 patients had CR–POPF [grade B–3(7.5%), grade C–2(5%)]. Pancreatic fistula in relation with duct size has attained statistical significance. When all the four factors were put together and given fistula risk score, it correlated well with the occurrence of fistula. Fistula risk score has high negative predictive value. Of 40 patients, 13 patients fall into low risk zone, out of which 1 patient developed grade A fistula. 26 patients fall into moderate risk zone, out of which 4 patients developed grade A, 3 patients developed grade B and 1 patient developed grade C fistula. One patient fall into high risk zone and developed grade C fistula. Conclusions: We found in our study that, post-operative pancreatic fistulae could be modestly predicted using fistula risk score. However, the latter had high negative predictive value and thus could be used to prognosticate risk of non-development of fistula than predicting its severity.